TRAINING OF FOREIGN STUDENTS IN UKRAINE AS A FACTOR INTERNATIONALIZATION OF HIGHER EDUCATION - Hryshchuk, Yuliia (Continuing Professional Education: Theory and Practice, 2019)
The article considers the training of foreign students in Ukraine as a factor of the internationalization of higher education.Based on the analytical reports of the International Research Foundation of Educational Policy and CEDOS it is described the internationalEducational markets for Ukrainian universities.Markets of International Education for Ukrainian universities for the last 10 years have changed.The proportion of students from Iran and Malaysia significantly decreased since the Malaysian government stopped to recognize the Ukrainian medical diplomas of higher education.Reducing the number of students from Tunisia, Russia and Moldova due to their reorientation to Romanian universities.Romania became more attractive for foreign students after accession to the EU. Moreover, the Romanian universities began to open Francophoneprograms.At the same time the proportion of students from Azerbaijan and Turkmenistan has increased. The attractiveness of higher education for international students, which is largely reflected in their number should be considered as one of the performance criteria for universities.The attractiveness of higher education for international students is an important indicator of democracy and cultural pluralism of society.The entry of foreign students in educational space is a determining factor in the internationalization of higher education.Internationalization of higher education would expand academic and student mobility, ensuring accessibility of higher education quality assurance of higher education universalization of knowledge, increase innovation of higher education and the expansion of international cooperation. It is identified the preconditions of increasing the number of foreign students in Ukraine (ensuring participation in various programs of international mobility, diversification of language learning, creating opportunities for parallel national diploma of highereducational document of one of the EU countries, the use of modern technology and the benefits of distance learning, the development of educational franchising;increasing of transparency and strengthen of information policy).